The Fort Collins commuter study: Variability in personal exposure to air pollutants by microenvironment. (25th January 2019) - Koehler, Kirsten; Good, Nicholas; Wilson, Ander; Mölter, Anna; Moore, Brianna F.; Carpenter, Taylor; Peel, Jennifer L.; Volckens, John
Abstract: This study investigated the role of microenvironment on personal exposures to black carbon (BC), fine particulate mass (PM2.5 ), carbon monoxide (CO), and particle number concentration (PNC) among adult residents of Fort Collins, Colorado, USA. Forty‐four participants carried a backpack containing personal monitoring instruments for eight nonconsecutive 24‐hour periods. Exposures were apportioned into five microenvironments: Home, Work, Transit, Eateries, and Other. Personal exposures exhibited wide heterogeneity that was dominated by within‐person variability (both day‐to‐day and between microenvironment variability). Linear mixed‐effects models were used to compare mean personal exposures in each microenvironment, while accounting for possible within‐person correlation. Mean personal exposures during Transit and at Eateries tended to be higher than exposures at Home, where participants spent the majority of their time. Compared to Home, mean exposures to BC in Transit were, on average, 129% [95% confidence interval: 101% 162%] higher and exposures to PNC were 180% [101% 289%] higher in Eateries.